Perancangan dan Implementasi Sistem Manajemen Sekolah di SMKS Globe National Plus 2 Batam menggunakan Framework Scrum - Muhamad Dody Firmansyah; Christopher Khomali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
SMKS Globe National Plus 2 is one of the educational units with a SMK level that was established in 2017, the school still does not have a school management system. School activities related to students, teachers, and school employees are still carried out manually, where in its application this can be an obstacle including time effectiveness and efficiency, the report form is still in the form of hardcopy which can cause difficulties in finding data, and allows important data to be lost. . The methodology we apply in this research is applied research with the aim of solving the problems faced by SMKS Globe National Plus 2 Batam in this digital era. The result of this research is a school management system.